2006
DOI: 10.4028/www.scientific.net/msf.527-529.363
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Stacking Fault-Induced Behavior in 4H-SiC p-i-n Diodes

Abstract: Formation of I1 Shockley stacking faults by recombination-enhanced defect glide in 4HSiC p-i-n diodes subject to high forward current stress is studied in diodes on both c-oriented and aoriented substrates. The forward voltage increases during stressing for both orientations, accompanied by nucleation and expansion of faults visible in electroluminescence (EL) imaging. Low temperature photoluminescence (PL) measurements on degraded diodes of both orientations reveal the same set of exciton peaks, confirming th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
0
0
1
Order By: Relevance
“…All results demonstrated that reducing BPDs of the substrate is especially important for reducing SFs in the epitaxial layers. Key words: SiC; homoepitaxial; dislocation; stacking fault SiC 是目前受到广泛关注的半导体材料, 具有 宽带隙、高击穿电场、高饱和电子漂移速度和高导 热性等优异性能, 是制作高温、高频、大功率和低 损耗器件的优良材料 [1][2][3] 。然而, 在 SiC 衬底中, 存 在各种缺陷 [4][5][6][7][8] , 如螺位错(TSD)、刃位错(TED)、基 平面位错(BPD)和堆垛层错(SF)。 这些缺陷在外延过 程中繁衍, 使得器件性能和可靠性降低 [9][10] 。 SiC 外延层中的堆垛层错是一种面缺陷, 会增 大二极管的反向漏电流以及降低击穿电压 [11][12][13][14] , 严 重影响了 SiC 器件的性能, 目前的研究认为六方 SiC 的堆垛层错主要起源于衬底缺陷。 Yamamoto 等 [15][16] 用 X 射线形貌法(X-ray Topography)证明了 SiC 外延 层的 SF 起源于衬底的 SF。Zhang 等 [10] 报道了外延 层中的两种 SF, 一种 SF 在(0001)面内传播形成基平 面 SF, 另外一种在垂直于(0001)的晶面内传播形成 棱镜面 SF, 它们起源于衬底的 BPD、TED 或 TSD。 Zhou 等 [17] 的研究证实 SiC 外延层中 3C-SF 起源于 衬底的 TSD, TED 或者应力, 在形貌上表现为三角 形。 Hassan 等 [18] 报道 SiC PiN 二极管中,衬底的 BPD 在外延过程中分解为两个不全位错(PDs), 在两个 不全位错之间形成肖特基型 SF。 Lijima 等 [19] 也报道 衬底的 BPD 在外延时产生 SF, 并且将外延层中 SF 的形貌与衬底中 BPD 的结构做了关联性研究。 Stahlbush 等 [20] 通过紫外光激发电子空穴对的方法, 间接证实了外延过程中 BPD 的移动产生了 SF。 Okojie 等 [21] [24][25] , 可能起源于衬底的 TSD、 TED、BPD、划痕、应力或其它。下面主要讨论 I-IV…”
unclassified
“…All results demonstrated that reducing BPDs of the substrate is especially important for reducing SFs in the epitaxial layers. Key words: SiC; homoepitaxial; dislocation; stacking fault SiC 是目前受到广泛关注的半导体材料, 具有 宽带隙、高击穿电场、高饱和电子漂移速度和高导 热性等优异性能, 是制作高温、高频、大功率和低 损耗器件的优良材料 [1][2][3] 。然而, 在 SiC 衬底中, 存 在各种缺陷 [4][5][6][7][8] , 如螺位错(TSD)、刃位错(TED)、基 平面位错(BPD)和堆垛层错(SF)。 这些缺陷在外延过 程中繁衍, 使得器件性能和可靠性降低 [9][10] 。 SiC 外延层中的堆垛层错是一种面缺陷, 会增 大二极管的反向漏电流以及降低击穿电压 [11][12][13][14] , 严 重影响了 SiC 器件的性能, 目前的研究认为六方 SiC 的堆垛层错主要起源于衬底缺陷。 Yamamoto 等 [15][16] 用 X 射线形貌法(X-ray Topography)证明了 SiC 外延 层的 SF 起源于衬底的 SF。Zhang 等 [10] 报道了外延 层中的两种 SF, 一种 SF 在(0001)面内传播形成基平 面 SF, 另外一种在垂直于(0001)的晶面内传播形成 棱镜面 SF, 它们起源于衬底的 BPD、TED 或 TSD。 Zhou 等 [17] 的研究证实 SiC 外延层中 3C-SF 起源于 衬底的 TSD, TED 或者应力, 在形貌上表现为三角 形。 Hassan 等 [18] 报道 SiC PiN 二极管中,衬底的 BPD 在外延过程中分解为两个不全位错(PDs), 在两个 不全位错之间形成肖特基型 SF。 Lijima 等 [19] 也报道 衬底的 BPD 在外延时产生 SF, 并且将外延层中 SF 的形貌与衬底中 BPD 的结构做了关联性研究。 Stahlbush 等 [20] 通过紫外光激发电子空穴对的方法, 间接证实了外延过程中 BPD 的移动产生了 SF。 Okojie 等 [21] [24][25] , 可能起源于衬底的 TSD、 TED、BPD、划痕、应力或其它。下面主要讨论 I-IV…”
unclassified